Comparative Study of the Compressive Strength of SCC with Sika ViscoCrete 3155N and Sika SIKACIM Concrete using Destructive Testing - Azani, Ahmad Ali; Hariyadi, Hariyadi; Hamdani, Hafiz; Pascanawaty, Maya Saridewi (Journal La Multiapp, 2025)
Self-Compacting Concrete (SCC) is one of the key innovations in modern concrete technology, offering the ability to flow and fill formwork automatically without the need for mechanical compaction, made possible through the use of specialized chemical admixtures. This self-flowing property is derived from the high deformability of fresh concrete. To assess these characteristics, a slump flow test is conducted to evaluate the concrete’s ability to spread under its own weight. This study focuses on the uniformity of compressive strength in SCC incorporating two different types of admixtures. The concrete specimens were cylindrical, with a diameter of 15 cm and a height of 30 cm. Two types of superplasticizers SIKA ViscoCrete 3155N and SIKA Sikacim Concrete were used in the SCC mixtures for each sample group. Subsequently, the uniformity of the concrete was evaluated through destructive testing, specifically compressive strength testing, to determine the resulting compressive strength values. Based on the compressive strength tests conducted at 3 days of age, the following average values were obtained: the control (normal) concrete yielded an average compressive strength of 15.14 MPa; the SCC with 0.8% SIKA ViscoCrete 3155N achieved an average strength of 21.04 MPa; while the 2% dosage of the same admixture resulted in a lower average strength of 11.68 MPa. For SCC with 1% SIKA Sikacim Concrete, the average compressive strength was 12.78 MPa, and at 2% dosage, the average strength was 13.38 MPa.